The role of intellectual capital as a mediating variable in the influential relationship between knowledge management and competitive superiority: A case study of operating banks in Annaba, Algeria - Ghers, Malika Abed; Baali, Hamza (International journal of economic perspectives, 2024)
This study aims at identifying the role of intellectual capital in mediating the relationship between knowledge management and competitive superiority in the Algerian banks. The sample of this study is composed of 340 individuals from commercial banks operating in Annaba, using a questionnaire as the primary data collection tool which includes 52 items. The hypotheses of the study are tested based on Path Analysis and the structural equation model for mediation analysis, with SPSS V26 and AMOS V25. The research ends with a series of findings and recommendations, mainly the lack of a direct impact of knowledge management on achieving competitive superiority. However, there is a positive indirect impact of knowledge management on achieving competitive superiority when intellectual capital is present as an intermediate variable. The study recommends paying great attention to the development and preservation of intellectual capital. Furthermore, plans and strategies for achieving competitive superiority should focus on the quality and continuous improvement of services provided and the use of information and communication technology as a pillar of knowledge management.